Effect of cobalt compounds on stability of ferrates(VI) - Головко, Дмитрий Аркадьевич; Головко, Игорь Дмитриевич (Technology audit and production reserves, 2015)
Decomposition of ferrate(VI) in the presence of cobalt compounds in different oxidation states is investigated in the article. It is shown that the decomposition rate of the alkaline solution of sodium ferrate increases with the introduction of Со compounds in the system in conjunction with the following number: Co2O3−CoO(OH)−СоSO4·7H2O−Co(OH)2. The greatest effect is destabilizing substances which contain Co(II). It was established experimentally that Co(II) compounds in an alkaline environment are rapidly oxidized by ferrate(VI) anion preferably to cobalt oxyhydroxide СоО(ОН). If FeO42− concentration of is significantly higher than Co(II) concentration, as it happens in the majority of cases, the reaction between them is as follows: 3Со(OH)2+FeO42−+Н2О→3СоO(OH)+[Fe(OH)4]−+OH−. Therefore, Co(III) compound, instead of Co(II), may be regarded as catalysts of the ferrate decomposition. It was shown that the crystalline K2FeO4 and BaFeO4, containing impurities of cobalt as Co2O3, are more stable in comparison with solutions with similar concentration of cobalt compounds. The results are interested for the development of effective technologies for producing ferrate(VI) of various metals.